Modular construction applied to Social Housing: analysis of materiality, sustainability and architectural form - Nemer, Luciana; Silva , Felipe Gustavo; Gavina, Samanta; Teixeira , Rafael Motta; Oliveira, Kleber Adriano Andrade de (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective - The article aims to carry out a systematic analysis of a Social Housing Architecture Project (HIS), conceived as an Undergraduate Final Project (TCC) and awarded with participation in the exhibition "Council of Architecture and Urbanism (CAU) in Your City – Niterói." The study seeks to demonstrate how modular construction, integrated with principles of sustainability and bioclimatic architecture, can enhance the quality of social housing. Methodology - The research adopts a qualitative approach, based on a bibliographic review of secondary sources (books, book chapters, conference papers, and journal articles) and a detailed analysis of the case study, considering the design report, floor plans, sections, elevations, perspectives, and technical detailing of the project. Originality/relevance - The originality of the study lies in the simultaneous articulation of three themes still rarely explored in conjunction: modular construction (form and materiality), Social Housing, and sustainability. The article contributes to bridging a gap in the literature by proposing an integrated approach between construction technology and socio-environmental quality in housing production. Results - The results show that modular construction can be highly effective when the project is conceived based on bioclimatic architecture principles, thermal comfort, and energy efficiency. The analysis confirms the technical and qualitative feasibility of the proposal. Theoretical/methodological contributions - The study proposes a methodological reading that values architectural design as an analytical instrument, in addition to contributing theoretically to the debate on new design approaches in the field of HIS. It highlights the importance of incorporating environmental performance criteria and construction efficiency into the teaching and practice of social architecture. Social and environmental contributions - Among the main implications are the promotion of higher-quality housing for low-income populations, the encouragement of adopting sustainable solutions in housing production, and the appreciation of modular construction techniques that reduce environmental impacts and increase user comfort.